2014
DOI: 10.1021/es404557e
|View full text |Cite
|
Sign up to set email alerts
|

Chromium(III) Complexation to Natural Organic Matter: Mechanisms and Modeling

Abstract: 26Chromium is a common soil contaminant, and it often exists as chromium(III). However,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
118
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(126 citation statements)
references
References 48 publications
5
118
1
1
Order By: Relevance
“…As for isolated HA and FA, the mor and peat samples showed a pH dependent sorption behavior, giving a lower silver solubility with increasing pH (Figure 2). At the highest pH values the silver solubility increased again, probably due to the increasing solubility of NOM with increasing pH (from 14 to 106 mg L -1 in mor suspensions and from 13 to 29 mg C L -1 in peat suspensions), which favored complexation reactions in the solution phase 41 . The SHM was unable to predict the solubility of silver using the generic binding parameters of HA and FA, giving too high solubility at pH <5.…”
Section: Resultsmentioning
confidence: 99%
“…As for isolated HA and FA, the mor and peat samples showed a pH dependent sorption behavior, giving a lower silver solubility with increasing pH (Figure 2). At the highest pH values the silver solubility increased again, probably due to the increasing solubility of NOM with increasing pH (from 14 to 106 mg L -1 in mor suspensions and from 13 to 29 mg C L -1 in peat suspensions), which favored complexation reactions in the solution phase 41 . The SHM was unable to predict the solubility of silver using the generic binding parameters of HA and FA, giving too high solubility at pH <5.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have reported that NOM may affect the toxicity of nanoparticles by forming NOM-nanoparticle composites [1], may interact with inorganic contaminant in the environment to affect its environmental behavior [2], and may be a source of new contaminants during the chlorination processes of drinking water [3,4]. Because NOM molecules play a pivotal role in the cycling and transport of elements in the ecosphere and have other effects on the environmental quality, it is important for environmental chemists to better understand the molecular composition and transformation of NOM.…”
Section: Introductionmentioning
confidence: 99%
“…Complexation of the metals with DOC was modelled using the 'Stockholm humic model' (SHM) (Gustafsson et al 2014) with its default database. The DOC and major anions were not measured during the field campaign in 2012.…”
Section: Modelling Approachmentioning
confidence: 99%